Gene variants in the folate pathway are associated with increased levels of folate receptor autoantibodies. Issue 12 (6th May 2018) - Dong, Yuqi; Wang, Linlin; Lei, Yunping; Yang, Na; Cabrera, Robert M.; Finnell, Richard H.; Ren, Aiguo
Abstract : Background: Folate receptors (FRs) facilitate embryonic uptake of folates and are important for proper early embryonic development. There is accumulating evidence that blocking FR autoantibodies contribute to developmental diseases. However, genetic factors associated with the expression of FR autoantibodies remain unknown. Objective: We investigated the effects of genetic polymorphisms in folate pathway genes on FR autoantibody titers in women. Methods: We recruited 302 pregnant women in China. The FR antigen‐down immunoassay was used to measure levels of FR autoantibodies including human immunoglobulin G (IgG) and immunoglobulin M (IgM) in maternal plasma. Genotypes were identified by matrix‐assisted laser desorption/ionization time of flight mass spectrometry and polymerase chain reaction methods. General linear model was used to analyze the effects of genetic variants on FR autoantibody levels. Results: Significant associations were observed between genotypic variations and levels of FR autoantibodies. Plasma levels of FR autoantibodies in women with the TT genotype at MTHFR rs1801133 were significantly higher than those of women with the CC genotype (IgG: β = 0.62, 95% CI 0.21–1.04; IgM: β = 0.42, 95% CI 0.12–0.72). For DNMT3A rs7560488, the level of FR autoantibody IgG significantly increased in the TT genotype compared with CC genotype (β = 0.90, 95% CI 0.20–1.59). For MTHFD2 rs828903, genotype GG was associated with elevated levels of FR autoantibody IgM compared to the AA genotype (β = 0.60, 95% CI 0.10–1.10). No association was detected between genetic variants of the DHFR gene with FR autoantibodies levels. Conclusion: Genetic variations in MTHFR, DNMT3A, and MTHFD2 genes were associated with elevated plasma levels of FR autoantibodies.